RHABDOCHONA (RHABDOCHONA) ACUMINATA (NEMATODA) EM PEIXES (CHARACIFORMES, ACESTRORHYNCHIDAE) DO RESERVATÓRIO DE TRÊS MARIAS, ALTO RIO SÃO FRANCISCO, BRASIL - Correia Costa, Danielle Priscilla (2011)
Rhabdochona (Rhabdochona) acuminata (Molin, 1860) (Rhabdochonidae) parasitizes the intestine of several species of fish and it has a broad geographical distribution. The present study is the first to report adult specimens of this helminth in Acestrorhynchus britskii Menezes, 1969 and Acestrorhynchus lacustris Lütken, 1875 (Acestrorhynchidae), collected in the Três Marias reservoir, upper São Francisco River, State of Minas Gerais, Brazil. At the same locality, Rhabdochona sp. larvae were found in sympatric populations of forage fishes, Tetragonopterus chalceus Spix & Agassiz, 1829 and Triportheus guentheri (Garman, 1890) which are potential prey to the piscivorous Acestrorhynchids and they are mentioned as possible intermediate or paratenic hosts of this parasite species. The parasite indices of R. acuminata were not influenced by either sex or total length of these piscivorous hosts.